(untitled) (Global Journal of Computer Science and Technology, 2012)
Cloud computing is an emerging technology and it is purely based on internet and its environment It provides different services to users such as Software-as-a-Service SaaS PaaS IaaS Storage-as-a-service SaaS Using Storage-as-a-Service users and organizations can store their data remotely which poses new security risks towards the correctness of data in cloud In order to achieve secure cloud storage there exists different techniques such as flexible distributed storage integrity auditing mechanism distributed erasure-coded data Merkle Hash Tree MHT construction etc These techniques support secure and efficient dynamic data storage in the cloud This paper also deals with architectures for security and privacy management in the cloud storage environment